2016
DOI: 10.1371/journal.pone.0159275
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty2 Suppresses Epithelial-Mesenchymal Transition of Human Lens Epithelial Cells through Blockade of Smad2 and ERK1/2 Pathways

Abstract: Transforming growth factor β (TGFβ)-induced epithelial-mesenchymal transition (EMT) of lens epithelial cells (LECs) plays a key role in the pathogenesis of anterior subcapsular cataract (ASC) and capsule opacification. In mouse lens, Sprouty2 (Spry2) has a negative regulatory role on TGFβ signaling. However, the regulation of Spry2 during ASC development and how Spry2 modulates TGFβ signaling pathway in human LECs have not been characterized. Here, we demonstrate that Spry2 expression level is decreased in ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“… 37 We next tested whether downregulation of SDC-4 also abrogated the migratory effects of FGF on LECs by the wound healing assay. 26 We found that bFGF significantly increased LEC migration, which could be suppressed by SDC-4 KD ( Figures 3a and b ). In addition, the transwell assay showed that SDC-4 KD significantly suppressed cell migration towards the FGF-containing medium ( Figures 3c and d ).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“… 37 We next tested whether downregulation of SDC-4 also abrogated the migratory effects of FGF on LECs by the wound healing assay. 26 We found that bFGF significantly increased LEC migration, which could be suppressed by SDC-4 KD ( Figures 3a and b ). In addition, the transwell assay showed that SDC-4 KD significantly suppressed cell migration towards the FGF-containing medium ( Figures 3c and d ).…”
Section: Resultsmentioning
confidence: 75%
“…To determine the role of SDC-4 in FGF signaling, we knocked down SDC-4 in LECs by using RNAi as previously described. 26 We observed a significant downregulation of SDC-4 after SDC-4 siRNA transfection at both transcript and protein levels ( Supplementary Figure 1 ). Then, we performed a CCK-8 assay to evaluate cell proliferation.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Formation of ACO includes two stages: an early stage of LEC proliferation and a late stage involving EMT and ECM production. The LEC proliferation process is regulated by various cytokines and growth factors, such as IL-1, IL-6, transforming growth factor (TGF) and fibroblast growth factor (FGF), which are secreted by residual LECs and inflammatory cells424344. Hydrophobic IOL has a higher incidence rate of ACO than hydrophilic IOL, because hydrophobic surfaces tend to attract more remnant LECs and inflammatory cells to adhere and proliferate5645.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of structural and signaling proteins have been demonstrated to facilitate PCO development: Transforming growth factor (TGF)-β expression is increased in response to injury (3) and it has been demonstrated that TGF-β not only induces epithelial-to-mesenchymal transition (EMT) in LECs, but also regulates cell migration, which are each considered key events in the initiation of PCO (4). In addition to the canonical Mothers against decapentaplegic signaling pathway, which mediates essential functions of TGF-β, non-canonical signaling pathways also exist and are involved in cell type-or process-specific events (5).…”
Section: The Role Of Focal Adhesion Kinase In Transforming Growth Facmentioning
confidence: 99%